2007
DOI: 10.2202/1446-9022.1128
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Efficiency Incentives: Evidence from the England and Wales Water and Sewerage Industry

Abstract: This paper evaluates the impact of the tightening in price cap by OFWAT and of other operational factors on the efficiency of water and sewerage companies in England and Wales using a mixture of data envelopment analysis and stochastic frontier analysis. Previous empirical results suggest that the regulatory system introduced at privatization was lax. The 1999 price review signaled a tightening in regulation which is shown to have led to a significant reduction in technical inefficiency. The new economic envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 47 publications
2
30
0
4
Order By: Relevance
“…This finding is consistent with past studies by Bottaso and Conti (2003), Erbetta and Cave (2007) and Maziotis et al (2009) where the authors suggested that the tightened 1999/00 price review had a positive impact on companies' productivity indicating that both the most productive and the less productive firms had strong incentives to improve their productivity in order to regain economic profitability. Another study by Bottasso and Conti (2009) Another paper by Garcia and Reynaud (2003) estimates the benefits of efficient water pricing in France and finds small efficiency gains -roughly 0.4% of initial surplus.…”
Section: Discussion and Policy Implicationssupporting
confidence: 92%
“…This finding is consistent with past studies by Bottaso and Conti (2003), Erbetta and Cave (2007) and Maziotis et al (2009) where the authors suggested that the tightened 1999/00 price review had a positive impact on companies' productivity indicating that both the most productive and the less productive firms had strong incentives to improve their productivity in order to regain economic profitability. Another study by Bottasso and Conti (2009) Another paper by Garcia and Reynaud (2003) estimates the benefits of efficient water pricing in France and finds small efficiency gains -roughly 0.4% of initial surplus.…”
Section: Discussion and Policy Implicationssupporting
confidence: 92%
“…Stone and Webster (2004) and Bottasso and Conti (2009) state that the presence of overcapitalisation could result in a misspecified total cost function where the assumption is that firms can instantaneously vary the level of capital. Saal and Parker (2000) and Erbetta and Cave (2007) consider a total cost function through the use of parametric and non-parametric specifications respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data from the ASHE (Annual Survey of Hours and Earnings) could be considered but due to the lack of regional data, this would mean applying the same price index for all companies. Staff costs were obtained from the statutory accounts rather than the June Return (Erbetta and Cave, 2007) as those reported within the June Return only relate to direct labour. This is not a perfect measure as the statutory accounts relate to the group activities.…”
Section: Definition Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have evaluated the impact of privatization on the efficiency and productivity of water companies (Ashton, 2000;Parker, 2000, 2001;Marques, 2008). Other have focused on evaluating the impact of regulation on productivity growth (Saal and Reid, 2004;Erbetta and Cave, 2007;Saal et al, 2007;Bottaso and Conti, 2009;Maziotis et al, 2009;Portela et al, 2011;Maziotis et al, 2012Molinos-Senante et al, 2014Maziotis et al, 2015) Despite of the wide number of studies aimed toward assessing the productivity change of the regulated water industry in England and Wales, to the best of our knowledge, none of them extended their methodologies to setting the X factor for the English and Welsh water and sewerage regulated companies. Researchers have developed DEA (Coelli and Walding, 2006) or index-number approach Bernstein et al, 2006) to measure productivity growth and propose X factors in regulated industries that include the water supply industry in Australia, the electricity network in New Zealand, and the telecommunication industry in Peru.…”
Section: Introductionmentioning
confidence: 99%